Syndromes, Disorders and Maternal Risk Factors Associated With Neural Tube Defects (VI) - Chih-Ping Chen (Elsevier, 2008)
Neural tube defects (NTDs) may be associated with syndromes, disorders, and maternal and fetal risk factors. This article provides a comprehensive review of the syndromes, disorders, and maternal and fetal risk factors associated with NTDs, including maternal fumonisin consumption, periconceptional zinc deficiency, parental occupational exposure and residential proximity to pesticides, lower socioeconomic status, fetal alcohol syndrome, mutations in the VANGL1 gene, human athymic Nude/SCID fetus, and single nucleotide polymorphism in the NOS3 gene. NTDs associated with these syndromes, disorders, and maternal and fetal risk factors are a rare but important cause of NTDs. The recurrence risk and the preventive effect of maternal folic acid intake in NTDs associated with syndromes, disorders and maternal risk factors may be different from those of nonsyndromic multifactorial NTDs. Perinatal diagnosis of NTDs should alert doctors to the syndromes, disorders, and maternal and fetal risk factors associated with NTDs, and prompt thorough etiologic investigation and genetic counseling.